MicroRNAs in Bladder Outlet Obstruction: Relationship to Growth and Matrix Remodelling. (14th January 2016) - Ekman, Mari; Albinsson, Sebastian; Uvelius, Bengt; Swärd, Karl
Abstract: The discovery of microRNAs (miRNAs), which are 22 nucleotide RNAs that inhibit protein synthesis in a sequence‐specific manner and are present in a range of species, has born hope of new therapeutic strategies. miRNAs play important roles in development and disease, but they remain poorly studied in uropathologies beyond cancer. Here, we discuss biological functions of miRNAs in the lower urogenital tract. A special focus is on miRNAs that change in bladder outlet obstruction (BOO). This is a condition that affects nearly one third of all men over 60 years and that involves growth and fibrosis of the urinary bladder. Animal models of BOO, such as that in rat, have been developed, and they feature a massive 6‐fold bladder growth over 6 weeks. Using microarrays, we have charted the miRNAs that change during the time course of this process and identified several with important modulatory roles. We discuss known and predicted functions of miR‐1, miR‐29, miR‐30, miR‐132/212, miR‐204 and miR‐221, all of which change in BOO. The majority of the miRNA‐mediated influences in BOO are expected to favour growth. We also outline evidence that miR‐29 represents a key effector molecule in a generic response to mechanical distension that is designed to counteract exaggerated organ deformation via effects on matrix deposition and stiffness. We conclude that miRNAs play important roles in bladder remodelling and growth and that they may be targeted pharmacologically to combat diseases of the lower urinary tract.